Research on the Music Curriculum Standards for Primary and Secondary Schools in Modern China - Lin, Wang (Journal of Social Science and Humanities, 2026)
In order to conduct a more comprehensive and detailed study on the development of music education in China and to provide references and comparative materials for the better development of contemporary music curriculum reform, this paper adopts the literature method. It takes the development of modern and contemporary music curriculum standards and the discussions of relevant scholars on these standards as the research objects. The literature on music curriculum and curriculum standard revisions by modern and contemporary musicians is selected for review, providing historical references for the construction of contemporary school music curriculum.